EIF SME Access to Finance Index - June 2019 Update - Wouter Torfs (European Investment Fund (EIF), 2019)
This EIF Working Paper elaborates on the most recent update2 of the EIF SME Access to Finance (ESAF) Index, a composite indicator that monitors SME external financing markets in the 28 EU countries. The ESAF was developed by EIF in collaboration with the London School of Economics. The 2018 ESAF ranking is headed by Sweden, with Germany and Finland completing the top 3. Greece lags the ESAF ranking for the sixth consecutive year in a row, preceded by Cyprus and Romania. The current update constitutes the sixth iteration of this exercise, resulting in a 6-year time series that runs from 2013 to 2018. Because of the discontinuation of one of the ESAF's sub-indicators, the 2018 update re-evaluated the indicator set and consequently introduced a number of changes to ensure the consistency of future updates. The note provides some background information underlying the most recent ESAF results and discusses the impact of the adapted indicator set on the ESAF outcome.
Keywords: 330